Social influences pondok pesantren terhadap perilaku konsumsi islami santri mahasiswi pondok pesantren syaichona moh. Cholil bangkalan - Dian Amalia; Muhaimin . (STAI Syaichona Moh. Cholil Bangkalan, 2017)
The main purpose of consumption for a Muslim is as a means of help to worship God. In this day and age there has been a growing behavior that consumerism is actually less useful. The nature of consumerism students along with the development and change of time can no longer be arrested. The purpose of this study to analyze social influences on the pattern of Islamic student consumption. In this research, quantitative research design is used. The sample of research is 52 female students of The Islamic Boarding School of Syaichona Moh. Cholil Bangkalan. Independent variable: social influence of boarding school (X) and dependent variable: Islamic consumption behavior (Y). The collection techniques used in this study is a questionnaire method. The analysis technique used in this research is simple linear regression. The results showed that most respondents considered social influences with enough frequency 35 people (67%), most of the respondents in the consumption behavior of female students of The Islamic Boarding School of Syaichona Moh. Cholil Bangkalan, quite in accordance with the frequency of 27 people (52%), and there is a significant influence between social influences with the behavior of Islamic consumption student of The Islamic Boarding School of Syaichona Moh. Cholil Bangkalan. Tighter supervision needs to be done cottage boarding school, to behave student consumption to conform with Islam. In addition, the self-control of the consumption of goods that are less appropriate to the needs and distinguish kosher and excessive consumption for female students.